2000
DOI: 10.1177/0887302x0001800201
|View full text |Cite
|
Sign up to set email alerts
|

Clothing and Identity Among Female In-line Skaters

Abstract: Role and identity theories provided perspective for this exploratory study of the needs and preferences of consumer athletes who participate in an emerging sport, in-line skating. Female in-line skaters (N = 54) were surveyed in Ohio and Florida regarding their skating commitment, sport clothing interests and preferences, and skating behaviors. Greater interests in achieving a unique and feminine appearance for performance enhancement and greater desire for fashion rather than comfort significantly predicted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 16 publications
3
75
2
2
Order By: Relevance
“…Therefore, the expressive consideration was not suitable to assess all martial arts uniforms together in the current study. In addition, empirical studies have indicated that functional performance and aesthetic appearance, rather than expressive consideration, are essential factors for sportswear (Dickson and Pollack 2000). Furthermore, to fit individual study contents, many empirical studies have also excluded expressive considerations (e.g., Jin and Black 2012;Michaelson 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the expressive consideration was not suitable to assess all martial arts uniforms together in the current study. In addition, empirical studies have indicated that functional performance and aesthetic appearance, rather than expressive consideration, are essential factors for sportswear (Dickson and Pollack 2000). Furthermore, to fit individual study contents, many empirical studies have also excluded expressive considerations (e.g., Jin and Black 2012;Michaelson 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…First, to assess martial arts practitioners' satisfaction with their current uniforms, functional and aesthetic variables of the current uniforms were chosen based on the FEA model and previous literature (Dickson and Pollack 2000;Lamb and Kallal 1992). In the current study, functional attributes included quality, fit, comfort, and protection; aesthetic attributes included fashion.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Dress is an important part of gender identity (Goodman et al, 2007) so the ways that standard competition dress make Toni (and other larger women) feel masculine is unsettling for her. Feeling uncomfortable and unattractive in competition clothes can have detrimental effects on sporting performance (Dickson & Pollack, 2000;Steinfeldt et al, 2013) so the lack of diversity in style and cut in equestrian competition dress may unfairly disadvantage some female riders.…”
Section: Individual Rider Identitiesmentioning
confidence: 99%
“…Appearance is a primary form of communicationdeliberate and not deliberate -in the construction of identities at individual and group levels (Strauss, 2003;Hansen, 2004). Sporting dress has to be functional, maximising performance for elite and grassroots athletes, but it must also be comfortable and aesthetically pleasing, providing the wearer with a sense of herself as an athlete, and specifically identifying her with her chosen sport, team or other affiliation (Wheat & Dickson, 1999;Dickson & Pollack, 2000). Sporting dress can both empower and undermine athletes, having consequences for athletic performance (Steinfeldt et al, 2013), and so a large industry has built up around active sportswear.…”
Section: Introductionmentioning
confidence: 99%